INTERNATIONALISATION OF HIGHER EDUCATION IN EUROPE: BY EXPERIENCE OF BOLOGNA UNIVERSITY - Nadezhda V. Krasilnikova (Образование и наука)
The purpose of the research is to study and analyse the current trends in internationalisation of higher education in European countries; analyse the performance of the University of Bologna with regard to development and implementation of its internationalisation strategy as well as identify factors facilitating successful development of internationalisation and hindering this process.Methods. Theoretical methods – analysis of regulatory documents on development and reforming of higher education; documents of national and international organisations which activities are relevant to internationalisation of higher education; conference papers; and regulatory documents of the University of Bologna. Empirical methods – student surveys and interviews with the staff members of the University of Bologna, observation, methods of mathematical statistics.Results and scientific novelty. The study has identified and described the major recent changes in the process of internationalisation in Europe. The outcomes of the research reveal that internationalisation process aimed primarily at enhancing the quality of education and research has become a strategic focus of universities; emphasis is being given to providing all students with the opportunity to develop intercultural competencies. The results of the empirical study suggest that the development of internationalisation at the University of Bologna is focused on enhancing academic mobility of students, elaborating and implementing double / joint degree programmes, as well as developing international research activities. One of the factors driving this development is the development and monitoring of the implementation of the University’s internationalisation strategy. Difficulties in the implementation of this strategy are still related to financial issues, as well as foreign language competency of students and professors and their insufficient motivation to participate in academic mobility programmes and international research projects.Practical significance. Material, presented in the paper, can be useful to staff members of international relations departments as well as people doing theoretical and practical research on development of internationalisation of higher education. The outcomes of the research can be used by Russian universities in developing and implementing their internationalisation strategies.